Nasolabial aesthetics of patients with repaired unilateral cleft lip and palate: A comparison of three rating methods in two countries. Issue 8 (August 2018) - Nguyen, Van Thai; Nguyen, Toai; Jagomägi, Triin
Abstract: Objectives: The study aimed to compare nasolabial aesthetics of patients with unilateral cleft lip and palate (UCLP) treated in Vietnam and Estonia using three rating methods: five-point aesthetic index, a visual analogue scale (VAS), and reference scores method. Methods: A total of 56 patients with repaired UCLP (23 from Vietnam and 33 from Estonia) were included in this cross-sectional study. Patients' facial and profile photographs were cropped to reveal the nasolabial region and coded. Five examiners rated nasolabial aesthetics of the patients using three methods: five-point aesthetic index, 100 mm VAS, and reference scores method. Intraclass correlation coefficients were used to evaluate intrarater and interrater reliabilities. Results: The five-point aesthetic index had a higher reliability than VAS and reference scores method. The least aesthetic feature among Vietnamese and Estonian patients was nasal symmetry and nasolabial profile respectively. No differences in nasolabial aesthetics were found between Vietnamese and Estonian patients regardless of the rating methods (p > 0.05) except for nasal symmetry. Conclusions: The five-point aesthetic index seems to produce more reproducible results. There were no significant differences in nasolabial aesthetics between the two countries. Overall average nasolabial appearance results were obtained using different treatment protocols in the two countries.